Dual stimulation using corifollitropin alfa in 54 Bologna criteria poor ovarian responders – a case series. Issue 5 (May 2019) - Alsbjerg, Birgit; Haahr, Thor; Elbaek, Helle O; Laursen, Rita; Povlsen, Betina B; Humaidan, Peter
Abstract: Research question: What are the reproductive outcomes of Bologna criteria poor responders undergoing dual stimulation (DuoStim) and subsequent cryopreserved embryo transfer? Design: Case series of patients treated during the period August 2015 to March 2018 in a public fertility clinic. The study included 54 Bologna criteria poor responder IVF patients younger than 42 years receiving a follicular stimulation (DuoStim 1) followed by a luteal phase stimulation (DuoStim 2) within the same cycle, both stimulations being performed with corifollitropin alfa followed by a subsequent cryopreserved embryo transfer cycle. The primary endpoint was the number of oocytes retrieved in DuoStim 1 compared with DuoStim 2. The secondary endpoint was ongoing pregnancy rate (OPR) at 12 weeks of gestation. Results: The mean number of oocytes retrieved in DuoStim 1 and DuoStim 2 was 2.4 ± 2.1 versus 3.7 ± 2.6, respectively; thus, a total of 1.2 (95% CI, 0.46–1.96) more oocytes was retrieved in DuoStim 2 compared with DuoStim 1 ( P = 0.002). The OPR at 12 weeks was 20% (11/54) in this poor ovarian response population with a mean age of 36.7 years. Conclusions: Luteal phase stimulation results in more oocytes in poor responders compared with follicular phase stimulation. DuoStim, using corifollitropin alfa followed by individualized FSH dosing, appears to be an alternative to conventional follicular phase stimulation, decreasing the risk of cycle cancellation.